Efficient continuous-flow synthesis of novel 1,2,3-triazole-substituted β-aminocyclohexanecarboxylic acid derivatives with gram-scale production - Ötvös, Sándor B.; Georgiádes, Ádám; Mándity, István M.; Kiss, Lóránd; Fülöp, Ferenc (Beilstein Journal of Organic Chemistry, 2013)
The preparation of novel multi-substituted 1,2,3-triazole-modified β-aminocyclohexanecarboxylic acid derivatives in a simple and efficient continuous-flow procedure is reported. The 1,3-dipolar cycloaddition reactions were performed with copper powder as a readily accessible Cu(I) source. Initially, high reaction rates were achieved under high-pressure/high-temperature conditions. Subsequently, the reaction temperature was lowered to room temperature by the joint use of both basic and acidic additives to improve the safety of the synthesis, as azides were to be handled as unstable reactants. Scale-up experiments were also performed, which led to the achievement of gram-scale production in a safe and straightforward way. The obtained 1,2,3-triazole-substituted β-aminocyclohexanecarboxylates can be regarded as interesting precursors for drugs with possible biological effects.
Keywords: β-amino acids; click chemistry; continuous-flow; copper; flow chemistry; triazoles